“Broken, I Want a Serious Relationship”: The (Self-)Representation of Heterosexual Masculinities on Tinder in India - Singh Sneha (Gender Studies)
This paper will discuss the representation of heterosexual masculinities in online dating applications in India. By taking the example of men’s self-representation on Tinder, the paper talks about how Indian men perform masculinities online. After collecting 120 male daters’ self-introductions (or bios), a thematic analysis was conducted to examine the online representation of masculinities in urban India. The analysis reveals that hegemonic Indian masculinities that operate within the terms of emotional insensitivity and toughness are not extensively present; rather, most male daters tend to display themselves as balanced selves between “emotional sensitivity” and “ideal manhood.” Male daters represent themselves within a range of qualities that are highly valued by women. The paper notes that Tinder provides a space for some men to negotiate (and even challenge) the dominant discourses on hegemonic masculinities by allowing the men to enact sensitivity and vulnerability, traits that are more aligned with women’s needs and perspectives.